Implementation of Law No. 40 of 2009 Concerning Youth Development Policy in Medan City - Pardede, Piki Darma Kristian (Universitas Muhammadiyah Yogyakarta, 2020)
This research uses descriptive qualitative, by describing in detail the process of implementing policies related to the formulation of youth development policies. This research was conducted based on the Edward III policy implementation model, where Edward III assessed implementation policy with four variables in public policy namely Communication, Resources, dispositions or attitudes, and bureaucratic structure. It can be denied that the Medan Municipality Youth and Sports Agency has not yet implemented Law No. 40 of 2009 concerning optimal youth, especially in terms of giving attention to youth organizations in developing and empowering youth in their communities. This study also found Law No. 40 of 2009 concerning Youth has not yet got a place in the Department of Youth and Sports (Dispora) Medan as a leading and strategic leader, in the development of youth development in Medan. This causes youth development by the Medan City Youth and Sports Agency to proceed slowly in directing youth development policies to realize Medan City to be a City of Youth where is youth development one of the priority programs of the Ministry of Youth and Sports in improving the quality of youth standardization throughout Indonesia.